Updates on Osteoimmunology: What's New on the Cross-Talk Between Bone and Immune System - Ponzetti, Marco; Rucci, Nadia (Frontiers in Endocrinology, 2019)
The term osteoimmunology was coined many years ago to describe the research field that deals with the cross-regulation between bone cells and the immune system. As a matter of fact, many factors that are classically considered immune-related, such as interleukins (i.e. IL-6, -11,-17 and -23), tumor necrosis factor (TNF)-α, receptor-activator of nuclear factor kappa B (RANK) and its ligand (RANKL), nuclear factor of activated t-cell, cytoplasmatic-1 (NFATc1) and others have all been found to be crucial in osteoclast and osteoblast biology. Conversely, bone cells, which we used to think would only regulate each other and take care of remodeling bone, actually regulate immune cells, by creating the so-called “endosteal niche”. Both osteoblasts and osteoclasts participate to this niche, either by favoring engraftment, or mobilization of hematopoietic stem cells (HSCs). In this review, we will describe the main milestones at the base of the osteoimmunology and present the key cellular players of the bone-immune system cross-talk, including HSCs, osteoblasts, osteoclasts, bone marrow macrophages, osteomacs, T- and B-lymphocytes, dendritic cells and neutrophils. We will also briefly describe some pathological conditions in which the bone-immune system cross-talk plays a crucial role, with the final aim to portray the state of the art in the mechanisms regulating the bone-immune system interplay, and some of the latest molecular players in the field. This is important to encourage investigation in this field, to identify new targets in the treatment of bone and immune diseases.